A systematic review and meta-analysis on delaying surgery for urothelial carcinoma of bladder and upper tract urothelial carcinoma: Implications for the COVID19 pandemic and beyond - Leow, Jeffrey J.; Tan, Wei Shen; Tan, Wei Phin; Tan, Teck Wei; Chan, Vinson Wai-Shun; Tikkinen, Kari A. O.; Kamat, Ashish; Sengupta, Shomik; Meng, Maxwell V.; Shariat, Shahrokh; Roupret, Morgan; Decaestecker, Karel; et al. (Frontiers in Surgery, 2022)
Purpose The COVID-19 pandemic has led to competing strains on hospital resources and healthcare personnel. Patients with newly diagnosed invasive urothelial carcinomas of bladder (UCB) upper tract (UTUC) may experience delays to definitive radical cystectomy (RC) or radical nephro-ureterectomy (RNU) respectively. We evaluate the impact of delaying definitive surgery on survival outcomes for invasive UCB and UTUC. Methods We searched for all studies investigating delayed urologic cancer surgery in Medline and Embase up to June 2020. A systematic review and meta-analysis was performed. Results We identified a total of 30 studies with 32,591 patients. Across 13 studies (n = 12,201), a delay from diagnosis of bladder cancer/TURBT to RC was associated with poorer overall survival (HR 1.25, 95% CI: 1.09–1.45, p = 0.002). For patients who underwent neoadjuvant chemotherapy before RC, across the 5 studies (n = 4,316 patients), a delay between neoadjuvant chemotherapy and radical cystectomy was not found to be significantly associated with overall survival (pooled HR 1.37, 95% CI: 0.96–1.94, p = 0.08). For UTUC, 6 studies (n = 4,629) found that delay between diagnosis of UTUC to RNU was associated with poorer overall survival (pooled HR 1.55, 95% CI: 1.19–2.02, p = 0.001) and cancer-specific survival (pooled HR of 2.56, 95% CI: 1.50–4.37, p = 0.001). Limitations included between-study heterogeneity, particularly in the definitions of delay cut-off periods between diagnosis to surgery. Conclusions A delay from diagnosis of UCB or UTUC to definitive RC or RNU was associated with poorer survival outcomes. This was not the case for patients who received neoadjuvant chemotherapy.